Baboo's Dream = Babu Ka Khwab - Farida Mirza; Translation by Fahmida Riaz; Illustrations by Saba Mahmood (Karachi Oxford University Press, 2015)
From the strong, clear lines of folk tale-based illustrations that introduce concepts of line and circle, letters of the alphabet, sound words$1 (Bto folk tales coloured with local art forms, ecology lessons, and gripping adventure stories$1 (Bhistory and geography blend in narrative and picture.s
Include Illustrations.
Through pictures and words, these books offer children opportunities to experience several worlds$1 (Bof people, places, animals, birds, trees, colours, shapes, and ideas.s
Keywords: Children Stories - Pakistan -- Pakistan -- Children Stories